2019
DOI: 10.4049/jimmunol.1800422
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inflammatory Hypoxia and Prevalence of Glycolytic Metabolism in Progressing Herpes Stromal Keratitis Lesions

Abstract: Chronic inflammation in tissues often causes the development of hypoxia. Herpes stromal keratitis (HSK) is a corneal chronic inflammatory condition that develops in response to recurrent HSV-1 infection. In this study, we investigated the development of hypoxia, the expression of hypoxia-associated glycolytic genes in HSV-1 infected corneas, and the outcome of blocking hypoxiainducible factor (HIF) dimerization on the severity of HSK. Our results showed the development of hypoxia, an elevated expression of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 58 publications
4
48
0
Order By: Relevance
“…65 Another setting where neutrophil infiltration creates a hypoxic microenvironment is during the development of herpes stromal keratitis, a chronic inflammatory condition of the cornea due to recurrent herpes simplex virus-1 infection. 66 However, in this case, hypoxia partly contributes to the progression of these lesions, with HIF-2ɑ becoming stabilized in the epithelial cells of these lesions, while HIF-1ɑ is stabilized in the infiltrating immune cells. Microenvironmental O 2 depletion during disease settings that involve heavy neutrophil infiltration is not always as a result of neutrophil respiratory burst, however.…”
Section: Consequences Of Hypoxic Microenvironments On Cell Migrationmentioning
confidence: 88%
“…65 Another setting where neutrophil infiltration creates a hypoxic microenvironment is during the development of herpes stromal keratitis, a chronic inflammatory condition of the cornea due to recurrent herpes simplex virus-1 infection. 66 However, in this case, hypoxia partly contributes to the progression of these lesions, with HIF-2ɑ becoming stabilized in the epithelial cells of these lesions, while HIF-1ɑ is stabilized in the infiltrating immune cells. Microenvironmental O 2 depletion during disease settings that involve heavy neutrophil infiltration is not always as a result of neutrophil respiratory burst, however.…”
Section: Consequences Of Hypoxic Microenvironments On Cell Migrationmentioning
confidence: 88%
“…Several factors such as TGF-β1, IGF-I, retinoic acid, TNF-α, and hypoxia are known to upregulate IGFBP-3 mRNA expression. [40][41][42] We recently showed the development of hypoxia in HSK-developing corneas, 43 suggesting a possibility that hypoxia might upregulate the expression of IGFBP-3 in HSK lesions. Once expressed, IGFBP-3 protein is secreted out of the cell but can be taken up in an autocrine or paracrine action through a variety of endocytic mechanisms involving caveolin-1 and clathrin-coated pits.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of neutrophils and CD4 + T cells are detected in the HSV-1infected corneal stroma. In the preclinical stage of HSK, increased expression of hypoxia-related glycolytic genes are detected in the corneas of HSV-1-infected mice, and viral replication in the infected cornea is triggered by innate immune responses during the early stage of infection, which induce neutrophil aggregation (143). Some studies have reported a correlation between hypoxia and inflammation.…”
Section: The Role Of Hypoxia In Hskmentioning
confidence: 99%
“…Moreover, tissue hypoxia can induce corneal angiogenesis, which aggravates visual impairment. Hypoxia inducible factors (HIFs) are present in the infected cornea, and blocking HIF-1α and HIF-2α expression with acriflavine can reduce the severity of HSK and induce regression of CNV (143). In summary, hypoxia plays an important role in HSK pathogenesis.…”
Section: The Role Of Hypoxia In Hskmentioning
confidence: 99%